2021
DOI: 10.3389/fcell.2021.612645
|View full text |Cite
|
Sign up to set email alerts
|

Slit/Robo Signaling Regulates Multiple Stages of the Development of the Drosophila Motion Detection System

Abstract: Neurogenesis is achieved through a sequence of steps that include specification and differentiation of progenitors into mature neurons. Frequently, precursors migrate to distinct positions before terminal differentiation. The Slit-Robo pathway, formed by the secreted ligand Slit and its membrane bound receptor Robo, was first discovered as a regulator of axonal growth. However, today, it is accepted that this pathway can regulate different cellular processes even outside the nervous system. Since most of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…This work, as well as our previous work and reports from other labs, present several arguments in favor of this idea: 1) there is no gradient observed in the larval optic lobe; 2) the slit mutant phenotypes can be rescued by expressing Slit in various cell populations, such as medulla neurons and, partially, in glia and photoreceptor cells ( Tayler et al, 2004 ; Caipo et al, 2020 ); and 3) large loss of function clones carrying the slit 2 allele in the visual system do not produce defects in optic lobe organization ( Tayler et al, 2004 ). Indeed, Slit expression does not show a restricted source in the larval optic lobe, and previous data show that it is expressed in multiple cell types ( Tayler et al, 2004 ; Caipo et al, 2020 ; Guzman-Palma et al, 2021 ), unlike in the central brain where it is enriched in the mushroom body ( Oliva et al, 2016 ) and the VNC where it is expressed in the midline ( Kidd et al, 1999 ; Dickson and Gilestro, 2006 ). Regarding the function of Robo receptors, the knockdown of all three Robo paralogues using a general driver resulted in defects in optic lobe development ( Tayler et al, 2004 ).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…This work, as well as our previous work and reports from other labs, present several arguments in favor of this idea: 1) there is no gradient observed in the larval optic lobe; 2) the slit mutant phenotypes can be rescued by expressing Slit in various cell populations, such as medulla neurons and, partially, in glia and photoreceptor cells ( Tayler et al, 2004 ; Caipo et al, 2020 ); and 3) large loss of function clones carrying the slit 2 allele in the visual system do not produce defects in optic lobe organization ( Tayler et al, 2004 ). Indeed, Slit expression does not show a restricted source in the larval optic lobe, and previous data show that it is expressed in multiple cell types ( Tayler et al, 2004 ; Caipo et al, 2020 ; Guzman-Palma et al, 2021 ), unlike in the central brain where it is enriched in the mushroom body ( Oliva et al, 2016 ) and the VNC where it is expressed in the midline ( Kidd et al, 1999 ; Dickson and Gilestro, 2006 ). Regarding the function of Robo receptors, the knockdown of all three Robo paralogues using a general driver resulted in defects in optic lobe development ( Tayler et al, 2004 ).…”
Section: Discussionmentioning
confidence: 93%
“…It has been previously shown that Slit and the three Drosophila Robo receptors are expressed in the medulla neuropil in addition to other regions of the visual system ( Tayler et al, 2004 ; Suzuki et al, 2016 ; Caipo et al, 2020 ; Guzman-Palma et al, 2021 ). Furthermore, in our previous work, we demonstrated that Ey + medulla neurons in the optic lobe are an important source of Slit ( Caipo et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations